Holistic energy healing practices: A preliminary study from an Islamic perspective - Awang, Abd. Rahman; Abdullah, Jariah (2010)
Healing is a mysterious process. It may come instantly or gradually, or it never happens. Healing may come in the simplest forms, such as a smile, specific words, love etc. It can also come through many mediums or techniques. disease can be defined as the state of not being at ease, and not beiing in alignment. According to one Al-Hadith "Every disease has a cure". Holistic energy is used from various sources: SHE(Spiritual Healing Energy), herbs, flowers, crystals, music, acupuncture, cupping, and NLP(Neuro Linguistic Programming). The experience tells that almost all patients have spiritual, emotional or mental misalignments. In SHE therapy the energy flows from the practitioner's hand into the patient's body in order to heal him. SHE has its roots from "Usui Reiki" and has been changed with new symbols and attunement techniques in accordance with the Islamic teachings. For example, symbol of Sei He Ki (peace) replaced with Al-Salam (peace). In addition, the music, with the energy of pray and positive words, is also used as Al-Farabi used to treat his patients. Moreover, Aura and Chakras will also be employed. The Five Principles of Reiki and the Six principles of SHE will be discussed in accordance with the Islamic views. The technique of applying SHE for healing oneself, others, animals, plants, food, storm, heavy rain, pain-relief and others will be discussed. The scanning on the roots of the health problems will also be demonstrated. The method of transferring the energy to water, crystal, eggs and music to release the negative energy will be explained. SHE can also complement other treatments without hindering them. It is very useful for anyone to obtain this energy in order to heal/treat him and for the humanity and the environments. The above issues and treatments will be analysed in accordance with the Islamic perspective.